Polyamine Homeostasis in Wild Type and Phenolamide Deficient Arabidopsis thaliana Stamens - Fellenberg, Christin; Handrick, Vinzenz; Ziegler, Jörg; Vogt, Thomas (Frontiers in Plant Science, 2012)
Polyamines like putrescine, spermidine, and spermine are ubiquitous polycationic molecules that occur in all living cells and have a role in a wide variety of biological processes. High amounts of spermidine conjugated to hydroxycinnamic acids are detected in the tryphine of Arabidopsis thaliana pollen grains. Tapetum localized spermidine hydroxycinnamic acid transferase (SHT) is essential for the biosynthesis of these anther specific tris-conjugated spermidine derivatives. Sht knock-out lines show a strong reduction of hydroxycinnamic acid amides (HCAAs). The effect of HCAA-deficient anthers on the level of free polyamines was measured by a new sensitive and reproducible method using 9-fluorenylmethyl chloroformate (FMOC) and fluorescence detection by HPLC. Polyamine concentrations can be accurately determined even when very limited amounts of plant material, as in the case of A. thaliana stamens, are available. Analysis of free polyamines (PAs) in wild type stamens compared to sht deficient mutants and transcript levels of key polyamine biosynthetic genes revealed a highly controlled regulation of PA homeostasis in A. thaliana anthers.